Nanofibrous carbon (multi-wall carbon nanotubes): synthesis and electrochemical studies by using field-effect transistor setup - Ildar A. Mustafin; Arslan F. Akhmetov; Renat B. Salikhov; Ilnur A. Mullagaliev; Timur R. Salikhov; Rail N. Galiakhmetov; Olga V. Shabunina; Dmitry S. Kopchuk; Igor S. Kovalev; Akhat G. Mustafin (Chimica Techno Acta)
Synthesis of nanofibrous carbon (multi-wall carbon nanotubes, MWCNTs) by means of n-hexane pyrolysis is reported. The structure of the obtained MWCNTs was studied using scanning electron microscopy, and the diameters of 20–85 nm and lengths of 500–600 nm for these nanotubes were observed. By using the above mentioned MWCNTs field-effect transistors were fabricated on ITO glass substrates with a gate dielectric made of 390 nm thick Al2O3 foil and the drain-source contacts made of 300 nm thick aluminum foil. The Nano-C film 200 nm thick was deposited by thermal evaporation in vacuum. The properties of the obtained field-effect transistors were studied. The current-voltage characteristics of the OFET show an increase in currents with a positive voltage on the gate, which corresponds to the electron conductivity of the transport channel. The dependences are nonlinear, and there are no saturation regions in the output characteristics. The Raman spectra indicate the presence of nickel and show characteristic peaks for C=C and CH bonds.